Care bundles of Traditional Chinese Medicine for a super-aged patient after interventional treatment for acute arterial embolization of lower extremity (1例超高龄急性下肢动脉栓塞患者术后集束化中医护理体会) - WANG Ting (王婷); HUANG Yanping (黄砚萍); FANG Xiaomei (方晓梅) (中西医结合护理)
This paper summarized the care bundles of Traditional Chinese Medicine (TCM) for a super-aged patient after interventional treatment for acute arterial embolization of lower extremity. Comprehensive TCM nursing interventions such as Chinese herbal medical oral care, acupoint massage, ear-tip bloodletting therapy; comprehensive auricular technique, Bian-stone and penetration of Chinese herbal medicine were carried out. TCM care bundles based on syndrome differentiation may reduce the incidence of complications and relieve the clinical symptoms of the patient. (本文总结1例超高龄急性下肢动脉栓塞患者术后集束化中医护理经验, 护理要点包括: 中药口腔护理、穴位按摩、耳尖刺络放血、耳穴综合操作技术、砭石熨摩中药透入法等。通过辨证施护, 有效降低并发症风险, 改善了患者症状, 舒适度和满意度明显提高。)